PERANCANGAN DESAIN ANTARMUKA APLIKASI PAKET PERNIKAHAN PADA SALON LIAN DENGAN METODE DESIGN SPRINT - Rochmat Rizky Alfandy; Endra Rahmawati; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Salon Lian or known as Lian Make Up is a service that serves to help the bride and groom in the wedding party. Lian's salon is located in Nganjuk, East Java. In ordering wedding packages, customers currently have to come directly to the Lian Salon location to get various information. Some customers find it difficult to order customized packages through the Instagram platform and failures often occur because the date to be booked is full. Currently in recording package orders, the owner still records in a simple way, namely by writing in a book. Based on the existing problems, the researcher will design an interface design for ordering wedding packages at Salon Lian according to user needs. The users are admin, owner and customer. The method used is the Design Sprint which has 5 stages starting from Map, Sketch, Decide, Prototype, and Validate. At the stage Mapping, analysis is carried out, while at the Sketch to Prototype stage it is the design stage. Furthermore, at this stage, the Validate author uses the method System Usability Score with the results obtained 74.0 which is included in the high margin with an adjective rating of GOOD as well as in-depth interviews involving prospective users in terms of interface design comfort according to user needs.